(untitled) (Research, Society and Development, 2023)
In recent years, babassu (Orbignya phalerata Martius) has increased its importance among the country’s renewable biomass resources, as it has a wide possibility of use. This palm tree can be found in much of Brazil, but it is Maranhão that concentrates almost all babassu almond production for the consumer market, followed by the states: Piauí, Pará, Bahia, Ceará and Tocantins. Its fruit, from which the oil is extracted, is responsible for almost 30% of the Brazilian production of vegetable extractivism, employing more than 2 million people. Babassu flour is produced from the pulp, albeit on a small scale. Due to its importance in Maranhão, the present work deals with the experimental study of the fluid dynamic behavior of babassu flour in a gas-solid fluidized bed. In this work, some of the main parameters of babassu fluidization were observed, among them the pressure drop at minimum (∆Pmf), minimum fluidization speed (Umf), fluidized bed porosity (ε). The objective of this was to study article the use of babassu mesocarp in a fluidized bed, aiming to identify, through the variation of the pressure drop in the bed as a function of the surface velocity of the gas, the fluidization regime and to characterize the fluid dynamic states. The results obtained showed that the babassu flour, for the operating conditions studied, behaved as a type A particle, according to the Geldart classification, with a minimum fluidization velocity estimated for the granulometries 53 µm, 125 µm and mix of 0,038 m/s, 0,084 m/s and 0,062 respectively and pressure drop at minimum fluidization which equals to 0,232 kPa, 0,28 kPa and 0,199 kPa.